Maize breeding enhances lodging resistance through vertical allocation changes of stem dry matter and nitrogen - Ruiz, Alejo; Listello, Agustin; Trifunovic, Slobodan; Archontoulis, Sotirios V. (Frontiers in Plant Science, 2025)
The maize stem provides structural support to other plant organs and stores carbohydrates and nitrogen (N) that can be remobilized to grain. Yet it remains unknown whether breeding programs have indirectly affected vertical stem dry matter and N allocation. Our objectives were to i) determine the dry matter and N allocations across different stem portions in maize hybrids released from 1980 to 2020 at the start (R2) and end of grain-filling period (R6), and ii) investigate the dry matter and N remobilization patterns by stem portion. We studied 23 Bayer Crop Science hybrids (release year 1980 to 2020) of different relative maturities (short and long maturity) in 2021 and 2022. Stem dry weight, N concentration, and N content by stem portion (four equal-length sections) were measured at R2 and R6 stages. We found that the average vertical distribution of the stem dry matter and N content along the plant height was 8% (top), 17% (middle-top), 29% (middle-bottom), and 46% (bottom). Maize breeding slightly reduced the total stem dry matter and N content at R2 stage in both relative maturities, and this reduction occurred in the top two quarters, with no significant change in the bottom stem portion. At R6 stage, the N content was significantly reduced in long maturity hybrids, and all the stem portions contributed to this reduction. Newer hybrids of both relative maturities remobilized less dry matter than the older hybrids (17 vs 20%) but slightly more N (39 vs 36%). We concluded that maize breeding efforts have indirectly affected vertical stem dry matter allocation towards less stem dry matter above the ear leaf. This change reduces plants’ center of gravity, which could explain why new hybrids are more resistant to lodging and can accommodate high plant densities. This study brings new data and knowledge, which enhances our understanding of indirect breeding consequences on maize plant traits.